The impact of e-cigarette smoking on the body and sport activity - a review of articles - Toczek, Martyna; Płusa, Alekasandra; Broda, Damian; Komissarova, Daria; Ciesielska, Izabela; Janczylik, Paulina; Głąb, Łukasz; Ryszka, Paulina; Cyls, Dawid (Quality in Sport, 2026)
This review article presents a thorough analysis of the available data regarding the effects of e-cigarette use on human health. The authors provide the current state of knowledge based on numerous clinical, laboratory, and observational studies. Special attention is given to the mechanisms of action of e-cigarettes and the chemical composition of the aerosol they generate, which - despite the absence of combustion - contains a number of potentially toxic compounds. The article discusses the effects of vaping on various body systems, including cardiovascular, respiratory, nervous systems, and the oral cavity. Additionally, the topic of the impact of physical activity is discussed.